ORGANIZATION OF INTERACTION OF BUDGETARY RESEARCH INSTITUTIONS WITH COMMERCIAL ENTITIES - S. Ulanin (Вестник университета)
Budget the successful interaction of research institutions with commercial organizations depends not only on the availability of the necessary infrastructure, but also on the organization of interaction of subjects of relations. The article reveals the organization of interaction on the basis of balance of economic interests of budgetary research institutions and commercial structures.